IMac for dummies - Chambers, Mark L. (--For dummies., 2019)
The perfect companion for iMac users You've got a great iMac, but now it's time to take things to the next level. This easy-to-use guide shows you how to do stuff like setting up and configuring your iMac along with fun stuff like using the Photos, Messages, and iMovie apps. You'll also discover how to get down to business with productivity apps like Numbers, Pages, and Keynote. Finally, you'll find help on how to sync everything to iCloud and stay organized with Family Sharing. Personalize your iMac and find your way around macOS X Surf the web, send Reminders, and make FaceTime video calls Store your photos and files with iCloud Discover tricks to become more efficient iMac newbies won & rsquo;t want to be without this easy-to-follow companion guide!